QARAQALPAQ HÁM INGLIS TILLERINDEGI GENDERLEKTTIŃ ÓZINE TÁN QASIYETLERI - Kurbanbaeva, D.M. (SCIENCE and SOCIETY, 2025)
In this article is discussed genderlect - the linguistic phenomenon of various gender-related speech patterns - is studied in two different linguistic and cultural contexts: Karakalpak and English. Based on sociolinguistic theory, pragmatic discourse analysis, and cultural semiotics, the article analyzes how men and women use language differently in these two languages.